Pengaruh Peer Group terhadap Disiplin Belajar Siswa - Barnawi, Barnawi (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2020)
Based on the results of the initial research, information was obtained that peer groups (peer groups) and student learning disciplines have varied relationships, students feel comfortable with their group friends, students feel alone when joining a non-group, students feel inferior, less active in learning when being grouped with students who are not of their own choice, forming gangs in the class, skipping lessons when learning, and influencing other students to violate the rules of learning in class. This study aims to find the effect of Peer Group on Student Discipline in the Subjects of Islamic Religious Education and Character Class VIII at SMPN 2 Gunung Jati, Cirebon Regency. The research design in this study uses a quantitative approach. The results showed that the R value obtained was 0.410, meaning that the correlation or r value between the peer group variable and student learning discipline was 0.410, this value when interpreted in the coefficient table the r value is classified as